PENGUNDERAITAN DALAM PRODUK TAKAFUL KELUARGA DARI PERSPEKTIF SYARIAH: Family Takaful Product Underwriting From Shariah Perspective - Mustafa, Aisyah; Ab Rahman, Asmak (Jurnal Syariah, 2015)
In the insurance operations, underwriting procesess are important to determine the premium rate that would be applicable to individuals who wanted to be insured. These processes involves the assessment and examination of the individual in order to fix the rates and risk classes. Takaful operators have known to have a similar practices with the insurance companies in the underwriting processes. Thus, all the issues facing by the insurance companies which are related to the underwriting processes may also occurs in the takaful industry. For example, in the conventional insurance, including gender and family background in the underwriting issues are seen as unfair by the insurance experts. Rigid underwriting processes can also restricted the participations into takaful plans. Strict evaluation in the application will cause the unhealthy applicants to be rejected. There is also a view that stated that the underwriting practices are against the concept of mutual help in takaful. Hence, to ascertain the importance of underwriting processes in takaful, literature research, encompassing books, papers and journals, were used to obtain information. A field study was also conducted by using the interview method. Interviews are conducted amongst the underwriters and a number of Shariah advisors from few takaful operators. The main focus of this study is to gain the Shariah’s insight on the underwriting practices, primarily to justify whether it is in accordance to the shariah principles. This analytical findings of this case study has concluded that the underwriting processes that currently being practiced in the takaful industry is in accordance with the Islamic principles.